2016
DOI: 10.1140/epjp/i2016-16109-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a vibrational energy harvester with a bistable beam: voltage response identification by multiscale entropy and “0-1” test

Abstract: Abstract. The use of bistable laminates is a potential approach to realize broadband piezoelectric-based energy harvesting by introducing elastic non-linearities to the system. In this paper the dynamic response of a piezoelectric material attached to a bistable laminate beam is examined based on the experimental measurement of the generated voltage-time series. The system was subjected to harmonic excitations and exhibited single-well and snap-through vibrations of both periodic and chaotic character. The abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The main motivation toward the development of new materials for the aviation industry is the reduction of aircraft weight, extending the time of reliable operation of the parts, improving fuel efficiency, and thus reducing aircraft operating costs [12][13][14]. These materials can be found in both internal and external aircraft constructions; in internal structures (secondary structures), they include cabins, floorboards, or armchairs, but it is the external (primary) structures that constitute the main market for composite aviation materials.…”
Section: Polymer Composites Used In Aviationmentioning
confidence: 99%
“…The main motivation toward the development of new materials for the aviation industry is the reduction of aircraft weight, extending the time of reliable operation of the parts, improving fuel efficiency, and thus reducing aircraft operating costs [12][13][14]. These materials can be found in both internal and external aircraft constructions; in internal structures (secondary structures), they include cabins, floorboards, or armchairs, but it is the external (primary) structures that constitute the main market for composite aviation materials.…”
Section: Polymer Composites Used In Aviationmentioning
confidence: 99%
“…The piezoelectric elements will obtain large strain and produce high electric power if the piezoelectric elements are attached to the surface of bi-stable laminate. Compared to using magnetic mechanism, this bi-stable energy harvester has four main advantages: (1) the arrangement can be designed to occupy a smaller space; (2) there are no magnetic fields; (3) the laminate can be easily combined with piezoelectric materials; (4) there is potential to control over harvester response through adjusting lay-up and geometry [19].…”
Section: Bi-stable Composite Laminatementioning
confidence: 99%
“…The results showed that the bi-stable harvester had higher power output over a broader range of frequencies at low frequency and low excitation and the linear one had the potential to produce a higher peak power but at a narrow bandwidth. In 2016, Harris et al [19] continued their work and investigated the dynamics of this bi-stable energy harvester by multiscale entropy and "0-1" test. As before, these oscillation modes including single-well oscillation, periodic and chaotic intermittent snap-through and continuous periodic snap-through were captured in experiments.…”
Section: Energy Harvestingmentioning
confidence: 99%
“…Not only does the harvester need to match the ambient vibrations, but also the input energy should be transmitted to the piezoelectric material as efficiently as possible. This is especially the case where the ambient vibration energy is limited and the harvesting mechanism could potentially have a major influence on the vibration source itself [16,17]. This situation demands a high efficiency of transformation of the mechanical vibration energy into electrical energy.…”
Section: Introductionmentioning
confidence: 99%